Hyperechoic Content of the Fetal Colon Is Not Always Cystinuria-Case Report - Antje Knapke; Guylhène Bourdat Michel; Isabelle Marey; Pauline Le Tanno (Frontiers Media S.A., 2022)
Cystinuria is a recessively inherited genetic disease causing recurrent kidney stones with risk of kidney failure. The discovery of hyperechoic colonic content on an antenatal ultrasound is considered to be a pathognomic sign of cystinuria. Herein, we present a clinical case with antenatal diagnosis of cystinuria in an ultrasound finding, which eventually revealed a multisystem disease, characterized by the association of renal Fanconi syndrome, hyperinsulinemic hypoglycemia, and hepatic dysfunction. Genetic investigations evidenced the recurrent heterozygous missense HNF4A (p.Arg76Trp) variant. Our case report shows that antenatal hyperechoic colonic content can hide a complex proximal renal tubulopathy, and questions the genetic counseling provided to families in the antenatal period.